Plant growth promoting rhizobacterium (PGPR): An effective consortium for sandal (Santalum album L.) seed germination - Anjali, K S; Jijeesh, C M; Kunhamu, T M; Jamaludheen, V; Santhoshkumar, A V (Plant Science Today, 2026)
Plant growth promoting rhizobacteria (PGPR) is a consortium of beneficial microorganisms having broad spectrum of mechanisms promoting plant growth. Sandal (Santalum album L.) seeds, in general have poor and staggered germination which is a major constraint in nursery management. Seed biopriming with beneficial microbes is one of the cheapest and eco-friendly seed enhancement techniques resulting in rapid, uniform, high crop establishment and yield. Fresh mature sandal seeds were procured from the Nachivayal Reserve Forest, Marayur Sandal Division, Kerala, India. The trial was conducted in two factorial Completely Randomized Design (CRD) with different concentrations of PGPR II(25, 50, 75 and 100 %) and different duration of the treatment (1, 2, 3, 4, 6 and 8 days) as factors. The effect of post-priming storage of one day and one week was also analyzed. The trial results in positive responses with respect to the germination percentage and seedling establishment. The highest germination was obtained for the seeds bioprimed at 50 % for 3 days (76.6 %) for post-priming storage of one week and highest seedling growth was obtained for the seeds bioprimed at 100 % for post-priming storage of one day and at 50 % for 3 days for post-priming storage one week. Both germination and seedling characters are its peak at biopriming with PGPR II at 50 % for 3 days subjected to post-priming storage of one week and hence recommended as the best treatment.